Adipose-derived Human Perivascular Stem Cells May Improve Achilles Tendon Healing in Rats. Issue 10 (October 2018) - Devana, Sai K.; Kelley, Benjamin V.; McBride, Owen J.; Kabir, Nima; Jensen, Andrew R.; Park, Se Jin; Eliasberg, Claire D.; Dar, Ayelet; Mosich, Gina M.; Kowalski, Tomasz J.; Péault, Bruno; Petrigliano, Frank A.; et al.
Abstract: Background: Achilles tendon rupture is a common injury and the best treatment option remains uncertain between surgical and nonoperative methods. Biologic approaches using multipotent stem cells such as perivascular stem cells pose a possible treatment option, although there is currently a paucity of evidence regarding their clinical therapeutic use. Questions/purposes: The purpose of this study was to determine whether injected perivascular stem cells (PSCs) would (1) improve histologic signs of tendon healing (such as percent area of collagen); and (2) improve biomechanical properties (peak load or stiffness) in a rat model of Achilles tendon transection. Methods: Two subtypes of PSCs were derived from human adipose tissue: pericytes (CD146 + CD34 - CD45 - CD31 - ) and adventitial cells (CD146 - CD34 + CD45 - CD31 - ). Thirty-two athymic rats underwent right Achilles transection and were randomized to receive injection with saline (eight tendons), hydrogel (four tendons), pericytes in hydrogel (four tendons), or adventitial cells in hydrogel (eight tendons) 3 days postoperatively with the left serving as an uninjured control. Additionally, a subset of pericytes was labeled with CM-diI to track cell viability and localization. At 3 weeks, the rats were euthanized, and investigators blinded to treatment group allocation evaluated tendon healing by peak load and stiffness using biomechanical testing and percent area of collagen using histologic analysis with picrosirius red staining. Results: Histologic analysis showed a higher mean percent area collagen for pericytes (30%) and adventitial cells (28%) than hydrogel (21%) or saline (26%). However, a nonparametric statistical analysis yielded no statistical difference. Mechanical testing demonstrated that the pericyte group had a higher peak load than the saline group (41 ± 7 N versus 26 ± 9 N; mean difference 15 N; 95% confidence interval [CI], 4-27 N; p = 0.003) and a higher peak load than the hydrogel group (41 ± 7 N versus 25 ± 3 N; mean difference 16; 95% CI, 8-24 N; p = 0.001). The pericyte group demonstrated higher stiffness than the hydrogel group (36 ± 12 N/mm versus 17 ± 6 N/mm; mean difference 19 N/mm; 95% CI, 5-34 N/mm; p = 0.005). Conclusions: Our results suggest that injection of PSCs improves mechanical but not the histologic properties of early Achilles tendon healing. Clinical Relevance: This is a preliminary study that provides more insight into the use of adipose-derived PSCs as a percutaneous therapy in the setting of Achilles tendon rupture. Further experiments to characterize the function of these cells may serve as a pathway to development of minimally invasive intervention aimed at improving nonoperative management while avoiding the complications associated with surgical treatment down the line.